ZWYKŁY UŻYTEK ORAZ TYPOWE WŁAŚCIWOŚCI W PRZYPADKU TOWARÓW KONSUMPCYJNYCH - Koszowski, Maciej (Zeszyty Prawnicze, 2016)
NORMAL USE AND TYPICAL FEATURES IN THE CONTEXT OF CONSUMER SALE Summary The article addresses the issue of the so-called normal use and typical features of a good of a given type in the context of consumer sale. These two legal institutions – along with public statements on the specific characteristics of a consumer good – are decisive if the parties did not make any, express or presumed, arrangements as to the purposes that the good should be fit for and the qualities it should possess. That is, basing upon the aforementioned institutions, we determine whether, according to the law, a specific consumer good can, or cannot, be presumed to be in conformity with the contract of sale. Moreover, unless there is a situation in which the buyer knew or may reasonably be expected to have known of the good’s lack of conformity with the contract at the time the contract was concluded, the normal use and typical features of a good of a given type usually determine the minimum standards that goods delivered to the buyer have to meet in the situation when the parties reached an agreement as to these goods’ quality. Although a good’s utility for normal use seems to imply that it must have the typical features proper for the given type of good, the application of both the institution of normal use and typical features to determine whether or not a given good conforms to the contract of sale leaves no doubt that legally non-conformity with the contract also encompasses aesthetic defects or maintenance costs and other expenses incurred in connection with its use which are higher than the normal costs. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />